Design a model for Teaching Management Information Security System in various faculties of Libyan Universities (مجلة التربوي, 2025)
The technological environment today is fast pace which innovating constantly. However, these innovations in technology come with their own risks which were not seen in the past. These risks have increased the need for information security systems in order to protect organizations from cyber-crime. Information security systems are key in educational institutes since they can be a target of cyber-crimes due to the information they contain. The current study analyzed the information security systems in various faculties of Libyan universities in an attempt to design a model for teaching management information security systems. The data included a sample population of 123.Through statistical tests, it was found that participants in various faculties are not fully aware of the information security system and there is no policies applied on clear foundations in any of the faculties. This study recommended that new policies be devised which will help create awareness and implement better information system security. The proposed model consists of four pillars which include information security policy, access control, encryption, operations and monitoring. This model will ensure that Libyan universities are able to implement and keep their information systems safe from any sort of cyber-crimes.